2020
DOI: 10.1051/0004-6361/201936800
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV radiation and dense clumps in the molecular outflow of Mrk 231

Abstract: We present interferometric observations of the CN(1-0) line emission in Mrk 231 and combine them with previous observations of CO and other H 2 gas tracers to study the physical properties of the massive molecular outflow. We find a strong boost of the CN/CO(1-0) line luminosity ratio in the outflow, which is unprecedented compared to any other known Galactic or extragalactic source. For the dense gas phase in the outflow traced by the HCN and CN emissions, we infer X CN ≡ [CN]/[H 2 ] > X HCN by at least a fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 108 publications
5
20
0
Order By: Relevance
“…CN has been detected in the double outflows of the merger NGC 3256 (Sakamoto et al 2014) and more studies are required to understand its origin. Very luminous CN emission is also detected in the quasar-driven molecular outflow of Mrk 231 (Cicone et al 2019) where X(CN) > X(HCN), suggesting strong radiative impact on the outflowing dense molecular gas. C 2 H has been found in the starburst-driven outflow of Maffei 2 (Meier and Turner 2012) and also in the interface region between the molecular disk and ionized gas outflow of NGC 1068 (García-Burillo et al 2017).…”
Section: Importance Of Shocks X-rays and Cosmic Raysmentioning
confidence: 94%
See 2 more Smart Citations
“…CN has been detected in the double outflows of the merger NGC 3256 (Sakamoto et al 2014) and more studies are required to understand its origin. Very luminous CN emission is also detected in the quasar-driven molecular outflow of Mrk 231 (Cicone et al 2019) where X(CN) > X(HCN), suggesting strong radiative impact on the outflowing dense molecular gas. C 2 H has been found in the starburst-driven outflow of Maffei 2 (Meier and Turner 2012) and also in the interface region between the molecular disk and ionized gas outflow of NGC 1068 (García-Burillo et al 2017).…”
Section: Importance Of Shocks X-rays and Cosmic Raysmentioning
confidence: 94%
“…A recent study reveal very bright CN emission from the Mrk 231 outflow. This may be due to UV photons originating from star formation in the outflow itself, or from the quasar (Cicone et al 2019). González-Alfonso et al ( 2018) have recently argued that the high OH + abundances relative to OH, H 2 O, and H 3 O + measured from the Herschel spectra imply a high ionization rate that cannot be explained by the unattenuated hard X-ray flux measured in this object (Teng et al 2014).…”
Section: Quasar: Mrk 231mentioning
confidence: 95%
See 1 more Smart Citation
“…Krug et al 2010;Rupke & Veilleux 2011;Cazzoli et al 2016;Concas et al 2019;Roberts-Borsani 2020), cold molecular gas phase, using different transitions of CO, HCN and [C ii], for instance (e.g. García-Burillo et al 2014;Tadhunter et al 2014;Feruglio et al 2017;Aladro et al 2018;Michiyama et al 2018;Zschaechner et al 2018;Aalto et al 2019;Husemann et al 2019;Cicone et al 2020;Veilleux et al 2020), warm and hot molecular gas phase, using transitions in the mid-to near-infrared (Veilleux et al 2009;Davies et al 2014;Hill & Zakamska 2014;Riffel et al 2015;Emonts et al 2017;May et al 2018;Petric et al 2018;Riffel et al 2020) and ionised gas phase observed using the rest-frame optical emission lines such as the forbidden transitions of [O iii] λ5007 (e.g. Harrison et al 2014;Kakkad et al 2016;Zakamska et al 2016;Fiore et al 2017;Venturi et al 2018;Baron & Netzer 2019;Coatman et al 2019;Förster Schreiber et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution and multi-wavelength observations are therefore required to study outflows in detail (e.g. Emonts et al 2017;Pereira-Santaella et al 2018;Cicone et al 2020).…”
Section: Introductionmentioning
confidence: 99%